Essential basil oil effect (Ocimum basilicum L.) on cattle tick Rhipicephalus (Boophilus) microplus in in vitro experiments - Santos, Fernanda Carlini Cunha dos; Vogel, Fernanda Silveira Flores; Monteiro, Silvia Gonzalez (Semina: Ciências Agrárias, 2012)
The excessive use of acaricidal products induces environmental and human contamination, whereas there is also the selection of resistant tick's strains. Most of the chemical acaricides available in the market have low efficacy due intensive use and inadequate management of treatments. Thus, ecologically viable alternatives for the tick's control is a promising area of research. Herbal medicine has as fundamental issue the study of medicinal plants and their use in the control and treatment of human and animal diseases. This experiment has evaluated the in vitro efficacy of Ocimum basilicum essential oil on engorded teleogines of Rhipicephalus (Boophilus) microplus. Six concentrations of the oil (1; 5; 10; 25, 50; 100%) were tested, diluted in distilled water, using the engorged female immersion test. The inhibition of oviposition were 10; 26; 26; 33; 100 and 100%, the egg hatch were 75; 60; 80; 45; 0 and 0%, and the effectiveness of treatment 28; 38; 36; 62; 100 and 100%, respectively. The statistic evaluation was done by the linear regression test, and it was observed a significant association between the concentration of the oil and the inhibition of oviposition, egg hatch and effectiveness. The oil at 25% had higher than 50% of effectiveness, and at 50 and 100% had total inhibition of oviposition with maximum efficiency. According to the results, it is possible to conclude that the Ocimum basilicum oil had in vitro acaricidal action on R. (B) microplus teleogines, obtaining partial control of this parasite.